2020
DOI: 10.5152/iao.2020.7018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Cochlear Fistulas Caused by Chronic Otitis Media with Cholesteatoma

Abstract: The Journal of International Advanced Otology (J Int Adv Otol) is an international, peer reviewed, open access publication that is fully sponsored and owned by the European Academy of Otology and Neurotology and the Politzer Society. The journal is published triannually in April, August, and December and its publication language is English. The scope of the Journal is limited with otology, neurotology, audiology (excluding linguistics) and skull base medicine. The Journal of International Advanced Otology aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
1
9
0
2
Order By: Relevance
“…In the remaining 6 patients, the system was irregular and even chaotic. The observation of irregular matrix structure is consistent with the research carried out by means of the Scanning Microscopy Laboratory by A. Miodonski, who demonstrated a chaotic matrix system in all of the analyzed preparations with diagnosed chronic cholesteatoma of the middle ear [8]. This is due to the fact that the proliferation of keratinocytes in cholesteatoma is much less coordinated compared to normal epidermis, whose pattern is regular.…”
Section: Methodssupporting
confidence: 89%
“…In the remaining 6 patients, the system was irregular and even chaotic. The observation of irregular matrix structure is consistent with the research carried out by means of the Scanning Microscopy Laboratory by A. Miodonski, who demonstrated a chaotic matrix system in all of the analyzed preparations with diagnosed chronic cholesteatoma of the middle ear [8]. This is due to the fact that the proliferation of keratinocytes in cholesteatoma is much less coordinated compared to normal epidermis, whose pattern is regular.…”
Section: Methodssupporting
confidence: 89%
“…The sensorineural hearing loss may be secondary to the long-standing infection as previously noted in a correlative study [6]. Another study demonstrated that sensorineural hearing loss in such presentation could be due to a cochlear fistula caused by chronic otitis media with cholesteatoma [7]. It is likely the patient may have had an improved hearing result if a diagnosis and treatment had occurred prior to the onset of sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 74%
“…6 Another study demonstrated that sensorineural hearing loss in such presentation could be due to a cochlear fistula caused by chronic otitis media with cholesteatoma. 7 It is likely the patient may have had an improved hearing result if a diagnosis and treatment had occurred prior to the onset of sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%